Regorafenib for Patients with Metastatic Colorectal Cancer Who Progressed After Standard Therapy: Results of the Large, Single‐Arm, Open‐Label Phase IIIb CONSIGN Study. (6th September 2018) - Van Cutsem, Eric; Martinelli, Erika; Cascinu, Stefano; Sobrero, Alberto; Banzi, Maria; Seitz, Jean‐François; Barone, Carlo; Ychou, Marc; Peeters, Marc; Brenner, Baruch; Hofheinz, Ralf Dieter; Maiello, Evaristo; et al.
Abstract: Background: In the phase III CORRECT trial, regorafenib significantly improved survival in treatment‐refractory metastatic colorectal cancer (mCRC). The CONSIGN study was designed to further characterize regorafenib safety and allow patients access to regorafenib before market authorization. Methods: This prospective, single‐arm study enrolled patients in 25 countries at 186 sites. Patients with treatment‐refractory mCRC and an Eastern Cooperative Oncology Group performance status (ECOG PS) ≤1 received regorafenib 160 mg once daily for the first 3 weeks of each 4‐week cycle. The primary endpoint was safety. Progression‐free survival (PFS) per investigator assessment was the only efficacy evaluation. Results: In total, 2, 872 patients were assigned to treatment and 2, 864 were treated. Median age was 62 years, ECOG PS 0/1 was 47%/53%, and 74% had received at least three prior regimens for metastatic disease. Median treatment duration was three cycles. Treatment‐emergent adverse events (TEAEs) led to dose reduction in 46% of patients. Regorafenib‐related TEAEs led to treatment discontinuation in 9%. Grade 5 regorafenib‐related TEAEs occurred in <1%. The most common grade ≥3 regorafenib‐related TEAEs were hypertension (15%), hand–foot skin reaction (14%), fatigue (13%), diarrhea (5%), and hypophosphatemia (5%). Treatment‐emergent grade 3–4 laboratory toxicities included alanine aminotransferase (6%), aspartate aminotransferase (7%), and bilirubin (13%). Ongoing monitoring identified one nonfatal case of regorafenib‐related severe drug‐induced liver injury per DILI Working Group criteria. Median PFS (95% confidence interval [CI]) was 2.7 months (2.6–2.7). Conclusion: In CONSIGN, the frequency and severity of TEAEs were consistent with the known safety profile of regorafenib. PFS was similar to reports of phase III trials. ClinicalTrials.gov : NCT01538680 . Implications for Practice: Patients with metastatic colorectal cancer (mCRC) who fail treatment with standard therapies, including chemotherapy and monoclonal antibodies targeting vascular endothelial growth factor or epidermal growth factor receptor, have few treatment options. The multikinase inhibitor regorafenib was shown to improve survival in patients with treatment‐refractory mCRC in the phase III CORRECT ( N = 760) and CONCUR ( N = 204) trials. However, safety data on regorafenib for mCRC in a larger number of patients were not available. The CONSIGN trial, carried out prospectively in more than 2, 800 patients across 25 countries, confirmed the safety profile of regorafenib from the phase III trials and reinforced the importance of using treatment modifications to manage adverse events. Abstract : This article reports the results of the CONSIGN study, which was designed to characterize the safety of regorafenib in a large patient population, estimate progression‐free survival, and provide patients with treatment‐refractory metastatic colorectal cancer access to regorafenib before market authorization.